MODEL KONSEPTUAL PENGEMBANGAN PELABUHAN PERIKANAN SAMUDERA BUNGUS SEBAGAI PUSAT PENDARATAN IKAN TUNA - Suci Asrina Ikhsan; Iin Sholihin; Tri Wiji Nurani (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Development conceptual model of oceanic fishing port Bungus as landing tuna fish center was a system that involves various actors in development. The research objective had done were evaluation the performance of oceanic fishing port Bungus and create a conceptual models as tuna fish landing centers. Development of oceanic fishing port Bungus with soft system methodology (SSM), which saw the overall problems in fishing ports. The results of this study were four conceptual models to repair problems that occur in the present. The conceptual model was built by three aspects, the study of human resources and institutional aspects, service aspects, and facilities aspects. Implementation the conceptual models that can be done with a variety strategies, involving the entire actors such as government, fishermen and the processing industry.